2020
DOI: 10.1002/tox.22980
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circ_POLA2 promotes lung cancer cell stemness via regulating the miR‐326/GNB1 axis

Abstract: Circular RNAs (CircRNAs) are a group of noncoding RNAs that have essential function in the development and progression of various cancers. The expression pattern and function of circRNA in lung cancer is not fully understood. In the present study, we aimed to investigate the expression profiles and underlying mechanism of circRNA circ_POLA2 in lung cancer cell stemness. Circ_POLA2 was highly expressed in lung cancer tissues and predicted a poor prognosis in lung cancer patients. Knockdown of circ_POLA2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In a recent study, circ_POLA2 was reported to be significantly upregulated in lung cancer and positively regulated the stemness of lung cancer cells. 14 Moreover, mechanism studies showed that circ_POLA2 may upregulate G protein subunit beta 1 by serving as an endogenous competing RNA for miR-326. 14 This study is the first to explore the involvement of circ_POLA2 in AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, circ_POLA2 was reported to be significantly upregulated in lung cancer and positively regulated the stemness of lung cancer cells. 14 Moreover, mechanism studies showed that circ_POLA2 may upregulate G protein subunit beta 1 by serving as an endogenous competing RNA for miR-326. 14 This study is the first to explore the involvement of circ_POLA2 in AML.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Moreover, mechanism studies showed that circ_POLA2 may upregulate G protein subunit beta 1 by serving as an endogenous competing RNA for miR-326. 14 This study is the first to explore the involvement of circ_POLA2 in AML. We found that circ_POLA2 was upregulated in AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, circRNAs may serve as potential targets for EC treatment. A previous study described a novel circRNA, circ_POLA2, with congenic functions in lung and cervical cancers (13,14). Our previous study, using deep sequencing analysis revealed altered circ_POLA2 expression level in EC, with an inverse correlation with microRNA (miR)-31, which has also been associated with cancer biology (15).…”
Section: Introductionmentioning
confidence: 94%
“…Circ_POLA2 is significantly upregulated in lung cancer cells and tissues, and promotes lung cancer progression via miR-326/GNB1 axis. 48 GNB1 is a direct target of miR-326 and necessary for the miR-326-mediated suppression on the stemness of lung cancer cells. In conclusion, circ_POLA2 plays a potential regulatory role via regulating the miR-326/GNB1 axis in lung cancer cell stemness.…”
Section: Circrnas In Lung Cancermentioning
confidence: 99%